Plant design of pentaeryhtritol - Barretto, Jose M. (College of Engineering, 1961)
The proposed pentaerythritol plant la designed to operate at a daily capacity of three tons of technical grade product, which has been considered to be of vital importance In the alkyd resins industry. Pentaerythritol has decided advantages over its principal competitor, glycerol, as will be discussed in detail in our economic survey.